TINJUAN PADA PENERAPAN UNSUR MOTIF PARAHYANGAN PADA INTERIOR HOTEL DI BANDUNG - Rubai, Asfhiyatul Jannah; Hermawan, Ibrahim (Department of Interior Design, Faculty of Engineering, Lancang Kuning University, Indonesia, 2025)
Bandung City has a very dynamic tourism potential and creative industry. In addition, its mild climate, beautiful scenery, and cultural heritage make it a favourite destination for tourists. Hotels are also an important part of cultural tourism in Bandung. The use of hotel interior visuals is not only aesthetics but also an educational element about local cultural heritage for tourists who stay or visit. This research aims to analyse the application of Parahyangan motifs in the interior design of hotels in Bandung City. Hotels in the city centre were chosen due to their strategic location and represent local cultural values in the interior design. This research uses a qualitative method with a descriptive approach and content analysis. Data were collected through a literature review, photo documentation of the interiors, and analysis of the motif elements used. The results show that Parahyangan motifs, such as Merak Ngibing, are widely used in city centre hotels to enhance aesthetic value and strengthen local cultural identity. This application provides an interesting visual experience for tourists and serves as an educational medium to introduce the diversity of West Java batik motifs to the wider community. In conclusion, the application of Parahyangan motifs in hotel interior design in Bandung can elevate local cultural heritage while creating a harmonious modern atmosphere.